PRECAUTIONARY PRINCIPLE AS AN EPISTEMOLOGICAL PROBLEM - IS IT PROTECTING OR PARALYZING? - Onat Özgür (Felsefe Dünyası)
The precautionary principle is one of the principles which are intended to lead sustainable development in the world. Historically, it has evolved as a principle because of a need to prevent evitable harms that may arise from new technologies, products, innovations. We can summarize the precautionary principle as “Prevention is better than cure” or “Better safe than sorry.” There are both critics and supporters of the precautionary principle. Critics argue that it will slow down or stop development of technologies. In this paper, I argue that the precautionary principle protects us from any possible environmental harm, instead of paralyzing us regarding the implementation of new technologies and innovations. I discuss the precautionary principle as an epistemological problem, by answering the criticisms, and also by mentioning the historical evolution of the principle, its definition, its uses in the international agreements, and a case study.